CAN ETHNICALLY TARGETED ADVERTISING WORK FOR MALAY ADOLESCENTS?: THE MODERATING ROLE OF THE STRENGTH OF ETHNIC IDENTITY - Muhammad Mohsin Butt; Ernest Cyril de Run (Asian Academy of Management Journal, 2012)
This article expands the existing research on ethnic advertising by investigating young consumers' attitudes towards targeted/ non-targeted ethnic advertisements as well as the moderating role of the strength of ethnic identity in an Eastern society. Eight hundred adolescents from different states within Malaysia were recruited for this research. Data were analysed using a MANOVA, and an independent sample t-test was used to examine group differences based on their exposure to targeted/non-targeted advertising as well as the intensity of ethnic affiliation. The MANOVA results indicate a main effect for advertisement type and the strength of ethnic identity. However, the results reveal no significant interactions. Further analysis of the data suggests that, compared with non-targeted respondents, targeted advertisement respondents have more positive attitudes towards the advertisement and the brand represented as well as greater subsequent purchasing intent. Interestingly, no significant differences were found between strong and weak ethnic identifiers in terms of attitudes towards targeted/non-targeted advertisements.